THE ARMED CONFRONTATION IN AFGHANISTAN AND POLITICAL AND ECONOMIC DEVELOPMENT IN CENTRAL ASIA - SMAGULOV, Agybay (CENTRAL ASIA AND THE CAUCASUS, 2013)
The author looks at how the armed confrontation in Afghanistan affects the political and economic situation in Central Asia. First, Afghanistan, which became a seat of international terrorism and religious extremism, as well as a foothold of the armed Tajik and Uzbek opposition in the 1990s, has developed into the real threat of a violent regime change in Tajikistan and Uzbekistan. In Tajikistan, the U.N. and certain other regional countries acting as intermediaries have successfully integrated the opposition into the country’s peaceful development. The Uzbek opposition fighting on the side of the Taliban has been considerably weakened by the international counterterrorist coalition. A compromise was reached in Tajikistan through constitutional amendments that legalized the Islamic party; on the other hand, we cannot rule out the possibility that in a country with a predominant Muslim population, Islam, a legal political factor, might come to power through democratic elections (this has already happened in Egypt). The leaders of Uzbekistan chose a different road: instead of negotiations and compromises, they squeezed the armed opposition out of the country to Afghanistan. Operation Enduring Freedom practically reduced to naught the threats of extremist attacks very real in 1999 and 2000. The coming pull-out of the international coalition troops from Afghanistan and inevitable bout of civil war that will ensue are causing concern in the Central Asian states: them far from simple social and economic context might raise a high wave of Islamic radicalism. Second, instability in Afghanistan prevents diversification of foreign economic ties; it makes the construction of southward highways and railways, as well as power lines and gas pipelines, impossible. Afghanistan remains an insurmountable barrier on the trade route between the Central Asian countries and Kazakhstan, on the one hand, and the South Asian and Middle Eastern countries, on the other, and (which is even more important) blocks access to their seaports. The counterterrorist operation that began in 2001 failed: the United States is pulling out of the country leaving behind the same “Afghan threat,” which is causing the Central Asian states to look to Russia and China as possible guarantors of their security.